Defining Vascular Anatomy of Kidney and Variation among Potential Live Kidney Donors Using Spiral Computed Tomographic Angiography - Chalise, Pawan Raj; Luitel, Bhojraj; Chapagain, Suman; Poudyal, Sujeet; Pradhan, Manish Man; Gyawali, Prem Raj; Singh Shah, Dibya (Journal of Institute of Medicine Nepal, 2024)
Introduction This study measured the accuracy of spiral computed tomographic angiography (SCTA) in defining renal vascular anatomy and estimating the prevalence of renal vascular anomalies in live kidney donors. Methods This prospective clinical study included 400 live-related-donor nephrectomies from June 2017 to December 2023. Renal vascular anatomy was described after SCTA. Reporting included the number of renal arteries and veins. Analysis was done by considering intraoperative findings as “actual” findings and compared to preoperative SCTA images for their prediction. For donated side kidneys, the prevalence of vascular variations was calculated using surgical and SCTA findings. The non-donated side was evaluated using SCTA alone. Results Four-hundred live-donor nephrectomies were performed including 326 left and 74 right-sided cases. Of the 400 kidneys harvested, 429 renal arteries were detected out of which 414 arteries (96.5 %) were predicted by SCTA. Fifteen accessory renal arteries (1-2 mm) were identified at nephrectomy, which was not predicted. In two cases, SCTA was reported to have renal arterial stenosis (multiple in one and in mid-part in the other) which turned out to be normal intraoperatively. Similarly, 417 renal veins were detected in 400 harvested kidneys. Out of these, 408 renal veins (97.8 %) were predicted by SCTA. Two renal arteries were found in 161 Kidneys and three renal arteries were found in seven kidneys. In addition, two renal veins were found in 35 kidneys. Conclusion Spiral computed tomographic angiography provided a reliable and accurate assessment of renal vascular anatomy and its variations in live donor nephrectomy. Small accessory arteries were missed occasionally.